An Analysis of Students' Ability to Answer Reading Questions with HOTS - Afifatul Mahfuzah; Jufri Jufri; Fitrawati Fitrawati (Universitas Negeri Padang, 2019)
This article is aimed to describe the students’ ability in answering reading questions with HOTS and the mistakes made by the students in answering those questions. The population of this research was the eleven grade students at SMA N 3 Bukittinggi. The Students at XI MIPA 3 were chosen to be the sample of the research by using cluster random sampling. There were 36 students involved in this research. The instrument used in this research was reading test. In the reading test, the researcher provided the sample students five analytical exposition test with forty five multiple choice questions which is surrounded by analyzing, evaluating and creating questions. The indicators of the test were adopted from Bloom (1956) and Anderson Taxonomy (2001). Based on the result of this research, it was found that the students’ ability to answer reading questions with HOTS was fairly good. It was proved by the average score obtained by the students which are analyzing (75.78), evaluating (75.05) and creating (72.19). Furthermore, the most mistake made by the students was producing idea to solve problem.